Discovery of Orally Available Prodrugs of the Glutamate Carboxypeptidase II (GCPII) Inhibitor 2-Phosphonomethylpentanedioic Acid (2-PMPA) - Majer, Pavel; Jančařík, Andrej; Krečmerová, Marcela; Tichý, Tomáš; Tenora, Lukáš; Wozniak, Krystyna; Wu, Ying; Pommier, Elie; Ferraris, Dana; Rais, Rana; Slusher, Barbara S (Journal of medicinal chemistry, 2016)
2-Phosphonomethylpentanedioic acid (1, 2-PMPA) is a potent inhibitor of glutamate carboxypeptidase II which has demonstrated robust neuroprotective efficacy in many neurological disease models. However, 1 is highly polar containing a phosphonate and two carboxylates, severely limiting its oral bioavailability. We strategized to mask the polar groups via a prodrug approach, increasing the likelihood of passive oral absorption. Our initial strategy was to cover the phosphonate with hydrophobic moieties such as pivaloyloxymethyl (POM) and isopropyloxycarbonyloxymethyl (POC) while keeping the α- and γ-carboxylates unsubstituted. This attempt was unsuccessful due to the chemical instability of the bis-POC/POM derivatives. Addition of α,γ-diesters and α-monoesters enhanced chemical stability and provided excellent oral exposure in mice, but these mixed esters were too stable in vivo, resulting in minimal release of 1. By introducing POC groups on both the phosphonate and α-carboxylate, we synthesized Tris-POC-2-PMPA (21b), which afforded excellent release of 1 following oral administration in both mice and dog.
Keywords: psi; jaterní mikrozomy; Microsomes, Liver; techniky in vitro; Humans; Dogs; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; inhibitory proteas; neuroprotektivní látky; glutamátkarboxypeptidasa II; Antigens, Surface; Prodrugs; biologická dostupnost; antigeny povrchové; Administration, Oral; lidé; zvířata; myši; Neuroprotective Agents; Mice; Biological Availability; objevování léků; prekurzory léčiv; In Vitro Techniques; Glutamate Carboxypeptidase II; Animals; aplikace orální; Drug Discovery; Protease Inhibitors